'It will dictate how many children I will have"- Women's decision-making in pregnancy following a previous caesarean birth (CB). (January 2023) - Monis, Malitha; O'Connell, Rhona; Andrews, Tom
Abstract: Vaginal birth after caesarean (VBAC) is supported in systematic reviews (Wu et al., 2019 ) and national guidelines (RCOG,  2015 ) and women are expected to be involved in the decision-making process for either a repeat caesarean birth or planned VBAC. Aim: To develop a Grounded Theory (GT) of women's decision making of their birth choices in pregnancy following a previous caesarean birth (CB) Objective: To explore what determines women's birth choice and their decision making for birth following a previous CB. Design: Semi structured interviews with pregnant women were undertaken in order to develop a Glasserian Grounded Theory Setting: Antenatal clinics and wards in a large tertiary level maternity hospital. Findings: The theory of 'Mentalizing Possibilities' is a substantive theory which explains pregnant women's decision making about their birth choices after a previous CB. Women's main concern is to achieve a positive experience. The core category of 'Mentalizing Possibilities' explains how women process their previous experience, adapt to uncertainty and deal with the decisional conflict. There are behavioural and cognitive strategies which women use to go through this process. Conclusion: Women want a positive birth experience after a previous CB and require support and continuity in decision making to help them decide the optimal birth choice for their current pregnancy.